The Phenomenological Analysis of Teachers' Experiences in Implementing Learning Innovations Based on the Merdeka Curriculum (A Case Study of SMAN 3 Jambi City) - Pane, Maykel Rifandi; Muslim, Fachruddiansyah; Sahara, Sahara (The Future of Education Journal, 2025)
This study aims to analyze and describe in depth the experiences of teachers at SMAN 3 Jambi City in implementing learning innovations based on the Merdeka Curriculum. The Merdeka Curriculum requires teachers to act as adaptive, creative facilitators who are capable of creating learner-centered teaching processes. This research uses a qualitative approach with a phenomenological design through a case study at SMAN 3 Jambi City. Data were collected through in-depth interviews, classroom observations, and document analysis involving economics teachers, the principal, and the vice-principal for curriculum. The findings show that teachers have implemented various forms of learning innovations, including differentiated learning and the Project-Based Learning (PjBL) model through the Strengthening the Profile of Pancasila Students (P5) project. These innovations are supported by school facilities and professional development training for teachers. However, challenges were identified, such as the diverse abilities of students, limited time for project implementation, and suboptimal use of digital resources. This study emphasizes that teachers' innovations positively impact student engagement, critical thinking skills, collaboration, and creativity. The success of implementing the Merdeka Curriculum is highly influenced by teachers' adaptive competencies and sustained institutional support.